Preventing Escherichia coli for deer hunters - Castor, Colby; Bivins, C.; Brummett, M.; Clarkston, C.; Cotroneo, O.; Engle, K.; Ewing, B.; Flowers, T.; Jones, Cassandra K.; Trinetta, Valentina (My University, 2017)
Introduction: Escherichia coli is a pathogenic bacterium of major concern in the food processing industry. Scientists have made great strides in reducing the prevalence of E. coli in pork, beef, and chicken products, but there is hardly any research done on wild game meats such as venison. It may be possible to reduce the levels of E. coli in venison using spices like cinnamon and coffee. Purpose: This study is focused on reducing the amount of E. coli in venison by adding cinnamon and coffee grounds to the meat. Methods: Two treatments were applied to each meat sample in addition to positive and negative control samples. Three dilutions were prepared for each sample on culture plates for E coli, total colony, and yeast and mold. Three repetitions of each dilution were performed to ensure precise and accurate data was received. Results: 270 samples were tested for E. coli growth, of which, all averaged data sets revealed substantial growth, including those for the negative control set. It is worthy to note that the total amount of E. coli decreased over a period of 7 days yet there was no substantial difference from values initially received at the beginning of the experiment. Since the α-value for each plate type was above 0.05 which indicates a 95% confidence interval, we fail to reject the null hypothesis. Significance: Because we fail to reject the null hypothesis, this means that neither cinnamon or coffee is effective in reducing E. coli levels in venison.
Keywords: Fall 2017